Diarylsulfonamides and their bioisosteres as dual inhibitors of alkaline phosphatase and carbonic anhydrase: Structure activity relationship and molecular modelling studies. Issue 10 (15th May 2015) - al-Rashida, Mariya; Ejaz, Syeda Abida; Ali, Sharafat; Shaukat, Aisha; Hamayoun, Mehwish; Ahmed, Maqsood; Iqbal, Jamshed
Graphical abstract: Abstract: The effect of bioisosteric replacement of carboxamide linking group with sulfonamide linking group, on alkaline phosphatase (AP) and carbonic anhydrase (CA) inhibition activity of aromatic benzenesulfonamides was investigated. A series of carboxamide linked aromatic benzenesulfonamides1a –1c, 2a –2d and their sulfonamide linked bioisosteres3a –3d, 4a –4d was synthesized and evaluated for inhibitory activity against bovine tissue non-specific alkaline phosphatase (TNAP), intestinal alkaline phosphatase (IAP) and bCA II. A significant increase in CA inhibition activity was observed upon bioisosteric replacement of carboxamide linking group with a sulfonamide group. Some of these compounds were identified as highly potent and selective AP inhibitors. Compounds1b, 2b, 3d, 4d 5b and5c were found to be selective bTNAP inhibitors, whereas compounds1a, 1c, 2a, 2c, 2d, 3a, 3c, 4a, 4b, 4c, 5a were found to be selective bIAP inhibitors. For most active AP inhibitor3b, detailed kinetic studies indicated a competitive mode of inhibition against tissue non-specific alkaline phosphatase (TNAP) and non-competitive mode of inhibition against intestinal alkaline phosphatase (IAP). Molecular docking studies were carried out to rationalize important binding site interactions.